(untitled) (Fiep Bulletin - online, 2013)
Exploratory descriptive study, prospective, with a quantitative approach, performed in the Monsenhor Walfredo Gurgel hospital complex (HMWG), in the city of Natal/RN, aiming to characterize the accidents involving motorcycle drivers attended to in the HMWG emergency room. The population consisted of 371 motorcycle drivers, with data collected from October to December 2007. For data collection, we used an instrument containing closed questions related to the characterization of the victims and accidents. The results show that among 371 motorcycle drivers affected by traffic accidents, 328 (88.40%) were male, aged 18 to 24 with 148 (39.90%), married 176 (47.98%) with a monthly income of up to 2 minimum wages with 279 (75.20%). Regarding the characteristics of accidents involving motorcycle drivers, 172 (46.36%) happened in the afternoon shift; 94 (25.34%) of the accidents happened on Sunday; 200 (53.91%) of the victims suffered falls or vehicle rolling and 104 (28.03%) were involved in motorcycle-car collisions; 196 (53%) of the investigated individuals claimed to possess driver’s license (CNH); 245 (63,03%) were wearing a helmet in the time of the accident; 213 (57.41%) were not intoxicated, and among those that did 158 (42,59%), alcohol was the substance most consumed with 115 (98.10%). We conclude that for motorcycle drivers victimized by traffic accidents, age, gender, day of the week, type of accident, use of drugs and not wearing a helmet signal increases in the risk for these events. We thus hope this study to contribute with the formulation of strategies for the facing of these problems.